Akta Autentik Dijadikan Objek Gugatan? - Tampubolon, Alfrida Septebrina; Yudhantaka, Lintang (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
Act against law is an action carried out that is not in accordance with prevailing legal provisions, and the consequence of such action is harm to others, allowing the injured party to seek accountability from the perpetrator, as stipulated in Article 1365 of the Civil Code. One common act against law found today is related to authentic deeds. An authentic deed is a deed created in the presence of an authorized official, in accordance with the prescribed form in legislation, as stated in Article 1868 of the Civil Code. The authorized officials include Notaries and Land Deed Officials. Authentic deeds themselves have perfect evidentiary strength. However, in practice, actions contrary to the creation of the deed often occur, ranging from procedural defects to negligence by Notaries/Land Deed Officials and others. This study specifically discusses authentic deeds that are contested as act against laws, as seen in Supreme Court Decision Number: 193/PK/Pdt/2020